Atopic dermatitis is associated with active and passive cigarette smoking in adolescents - Kim, So Young (PLoS One, 2017)
OBJECTIVE: The relationship between passive smoking and atopic dermatitis has previously been reported, but few studies have simultaneously evaluated the association of atopic dermatitis with active and passive smoking. METHODS: The relationships between atopic dermatitis and active and passive smoking were evaluated in Korean adolescents. We used a large, representative, population-based survey (The Korea Youth Risk Behavior Web-based Survey) conducted in 2011 and 2012. Active smoking was classified into 3 groups (0 days, 1–19 days, and ≥ 20 days/month). Passive smoking was categorized into 3 groups (0 days, 1–4 days, and ≥ 5 days/week). Atopic dermatitis diagnosed by a medical doctor either during the past 1 month or during the participant’s lifetime was surveyed. Age, sex, obesity status, region of residence, economic level, and parental educational level of the participants were adjusted as confounders. Adjusted odds ratios (AORs) and 95% confidence intervals (CI) were calculated using multiple logistic regression analysis with complex sampling. RESULTS: A total of 6.8% (10,020/135,682) of the participants reported atopic dermatitis during the last 12 months. Active smoking was significantly associated with atopic dermatitis (previous 12 months) (AOR [95% CI] of smoking ≥ 20 days/month = 1.18 [1.07–1.29]; 1–19 days/month = 1.11 [0.99–1.23], P = 0.002). Passive smoking was also related to atopic dermatitis (previous 12 months) (AOR [95% CI] of smoking ≥ 5 days/week = 1.12 [1.05–1.20]; 1–4 days/week = 1.08 [1.03–1.13], P < 0.001). CONCLUSION: Atopic dermatitis was significantly associated with active and passive smoking in Korean adolescents.